Diabetes and You : A Comprehensive, Holistic Approach - Ali, Naheed 1981- (Lanham, Md. : Rowman & Littlefield, 2012)
This book presents a holistic approach to dealing with diabetes, emphasizing a whole body approach to regulating blood sugar and balancing physical and mental health.
pt. 1. Diabetes at a glance. Diabetes explained ; Types of diabetes -- pt. 2. Getting to know diabetes. Causes and symptoms ; Diagnosing diabetes ; Treatment options ; Juvenile diabetes -- pt. 3. Other manifestations. Diabetes and mental health ; Diabetes and heart health -- pt. 4. Dealing with diabetes. The diabetic's ultimate diet ; Pain management for the diabetic ; Staying motivated.
Includes bibliographical references (p. 219-231) and index.
Keywords: Diabetes; Diabetes -- Alternative treatment; Holistic medicine